The effect of branched-chain amino acid ingestion on physical performance during prolonged exercise - Velloza, Peter Edward (MRC/UCT RU for Exercise and Sport Medicine, 2017)
It has been hypothesized that an increase in the ratio of plasma tryptophan (TRP) to branched-chain amino acid (BCAA) concentrations may mediate an increase in cerebral serotonin synthesis, through an increased cerebral tryptophan uptake. It is postulated that the increased brain serotonin content may induce central fatigue during prolonged exercise. Until present, this postulate had not been subject to rigorous scientific testing during prolonged exercise. Therefore the aim of this study was to investigate whether ingesting a BCAA supplement during prolonged exercise improves physical performance and central fatigue. The use of such a supplement during prolonged exercise could then be expected to have a large effect on performance. Eight trained cyclists (VO₂ max= 61.9 ± 4.3 ml 02/kg/min) ingested, in random order, a drink containing either 10% carbohydrate (CHO), 10% CHO and 0.16% branched-chain amino acid (BCAA) or 0.16% BCAA. Every hour, for the duration of the exercise (4 hours, 55% VO₂ max) blood samples were analysed for amino acids, ammonia, free fatty acids, glycerol, glucose and insulin concentrations. Urine was analysed for urea and creatinine concentrations. Heart rate, oxygen consumption (VO₂), respiratory exchange ratio (RER) and rating of perceived exertion were also analysed. Thereafter, subject's 40km time trial performance and RPE was assessed on a Velodyne windtrainer. Central fatigue following the time trial was quantified using the Sternberg reaction-time paradigm. The serum concentration of the BCAA's declined as a result of the exercise, in the BCAA only trial. Tryptophan concentration, however, did not change during the exercise. The serum TRP:BCAA ratio increased (0.16 ± 0.06 to 0.20 ± 0.10; p≤0.05) in the CHO trial only. The BCAA trial differed from the two trials in which CHO was ingested because plasma ammonia and glucose concentrations did not increase, while free fatty acids (FF A's) and glycerol concentrations increased significantly (p≤0.05). The lower RER in the BCAA trials suggests a higher proportion of fat was oxidised in these trials, compared to the other two trials. Cycling performance, over a 40km time trial, (CHO= 68.59 ± 6.02; CHO+ BCAA = 68.00 ± 3.01; BCAA = 69.43 ± 5.35 min/sec), ratings of perceived exertion, submaximal or maximal heart rates, and mental performance were not different between trials. Data from this study appears to refute the thesis hypothesis that an increase in serum TRP:BCAA decreases physical performance and central fatigue, during prolonged exercise.